Empowering Democracy Through Internetization - Passaris, Constantine E. (HAPSc Policy Briefs Series, 2020)
This policy brief explores the challenges and opportunities congruent with the advent of internetization on the democratic landscape. Internetization is a new word that I have coined to describe our contemporary empowerment through global outreach and electronic connectivity. There is no denying that the 21st century has precipitated profound structural change and empowered democracy through digital capacity and electronic connectivity. This paper analyzes the impact of internetization on e-democracy, social media, civics education, non-governmental organizations and global outreach. It also addresses the consequences of internetization on cybersecurity threats, election tampering and the contemporary challenges associated with electronic voting. This policy brief concludes with a set of recommendations embracing a new governance architecture, adapting the machinery of governance to electronic capacity and a strategic list of public policy initiatives directed to enhance the role of internetization on the democratic landscape.